2008
DOI: 10.1002/jsfa.3309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cut‐type on quality of minimally processed papaya

Abstract: BACKGROUND: This research was undertaken to study the effects of different cut-types (cube, parallelepiped, cylinder and sphere) on the quality and shelf-life of papaya cv. Sunrise Solo. Physicochemical analyses were carried out during 10 days of storage at 4 • C to determine colour, firmness, pH, titratable acidity, total soluble solids, weight loss and vitamin C content. Microbiological analysis and sensory evaluation were also performed. RESULTS: Papaya spheres (1.55 cm radius) presented the most favourable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 45 publications
(25 reference statements)
4
2
0
1
Order By: Relevance
“…Cut type 2 showed a decrease in lightness, probably due to the greater processing leading to the decompartmentalisation of the enzymes and substrates, causing browning reactions. Such behavior is similar to that observed by Argañosa et al (2008) where the cylinder type cut showed greater decreases in luminosity. Means followed by the same uppercase letter in the column, for each variable and temperature, do not differ significantly (*P<0.05).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Cut type 2 showed a decrease in lightness, probably due to the greater processing leading to the decompartmentalisation of the enzymes and substrates, causing browning reactions. Such behavior is similar to that observed by Argañosa et al (2008) where the cylinder type cut showed greater decreases in luminosity. Means followed by the same uppercase letter in the column, for each variable and temperature, do not differ significantly (*P<0.05).…”
Section: Resultssupporting
confidence: 88%
“…Freshly processed 'Formosa' papayas stored at 4 °C and 8 °C did not show significant variation in the soluble solids contents in relation to the storage time and package type, all results were around 11 ºBrix, as can be seen in Table 1. The only variation was in the storage at 8 ºC where there was a slight decrease for cut type 2, which was similar to that observed by Argañosa et al (2008) No significant differences were observed in titratable acidity contents, for package or cut type (Table 1). In the 8 ºC storage there was an increase in titratable acidity during the storage period, caused by the maturation process.…”
Section: Resultssupporting
confidence: 84%
“…Firmness (N) of the potatoes was determined using a TA-XT plus texture analyzer (Stable Micro System, UK) according to the methodology described by Rahman & Al-Farsi (2005). Titratable acidity (TA) and weight loss (WL) were determined using the methodology by (Argañosa et al, 2008), and pH was assessed according to the methodology by Cheng et al (2007). Total soluble solids (TSS) of the potato pieces were determined using a hand-held refractometer (Abbe model 10450) as described by Dong et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…De acordo com os resultados obtidos o pH das amostras que passaram pelo tratamento com cobertura (T2, T3, T4 e T5) variaram de 4,53 a 4,91 após 15 dias de armazenamento, que foi ligeiramente inferior ao pH inicial de mamão da amostra controle (T1). O baixo pH é preferido em frutas frescas, pois permite controlar melhor o crescimento microbiano (Argañosa, Raposo, Teixeira & Morais, 2008), o que indica neste trabalho os baixos valores de crescimento de bolores e leveduras e psicrotróficos.…”
Section: D) Potencial Hidrogeniônico (Ph)unclassified